Great Performances : Creating Classroom-Based Assessment Tasks. - Lewin, Larry (ASCD, 1998)
''What grade did you give me?'' students often ask teachers, as if teachers randomly assign grades. Too many students do not understand the concept of connecting grades to an earned academic performance. Improving students' understanding of what their teachers expect them to do, how well they should be able to do it, and how they should go about accomplishing it is what this book is all about.